Evolusi Perikatan dalam Transaksi E-Commerce : Regulasi dan Implementasi di Indonesia - Gina Anggini; Gita Silva Pramesti; Hilda Chaerunisa; Ine Tustinaningsih; Irma Dwi Nurrohmah (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
This article explains the evolution of the development of e-commerce in Indonesia, as well as regulation and enforcement. Development of information and communication technology has a big impact on various aspects of life, including activities commercial. E-commerce by utilizing internet technology has changed the traditional buying and selling transaction paradigm becomes more effective and efficient. These technological advances have legal implications that need to be considerespecially regarding the legal relationship (bond) formed between the perpetrators economics and consumers in electronic commerce. This article examines challenges and efforts in developing regulations for participation in electronic commerce and implementing effective legal regulations for guarantee legal certainty for all involved. We look forward to this discussion can produce a more comprehensive understanding of the problem laws that arise in the e-commerce ecosystem in Indonesia and facilitate development of a legal framework that takes into account unique characteristics digital commerce.